BINARY HARD-SPHERE COLLOID-DROPLET MIXTURES WITH THE PYRITE-TYPE STRUCTURE - Vu, Minh Tu (Trường Đại học Đà Lạt, 2024)
We investigate the assembly of a binary mixture of patchy colloids and droplets into crystal structures by use of the space-filling principle and Metropolis Monte Carlo simulations. Here, colloids with six patches in an octahedral symmetry attract droplets, whereas the colloid-colloid and droplet-droplet pairwise interactions are purely hard-core repulsions. Within parameter space regions that allow for stable binary crystals, we find the formation of different structure types, which are colloidal analogs of the NaCl phase and pyrite (FeS2) phase, as a function of the droplet-to-colloid sphere diameter ratio. This finding is consistent with theoretical predictions. Notably, while the NaCl structure type is a commonly known structure of hard-sphere colloids and nanoparticles, the formation of the FeS2 structure type from colloidal dispersion has not been explored. Our approach suggests a potential route to obtain colloidal crystals with more complex structures.